2011
DOI: 10.1142/s021963521100283x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of catalase inhibition into the fourth cerebral ventricle on the Bezold-Jarisch reflex in spontaneously hypertensive rats

Abstract: Many studies have investigated the role of oxidative stress on cardiovascular system in the brainstem of spontaneously hypertensive rats (SHR). However, we do not know yet if catalase inhibition influences cardiopulmonary reflex (Bezol-Jarisch reflex). Thus, we aimed to evaluate the effects of central catalase inhibition on cardiopulmonary reflex in SHR. Males Wistar Kyoto (WKY) rats and SHR were implanted with a stainless steel guide cannula into the fourth cerebral ventricle (4th V). The femoral artery and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We therefore consider that central catalase inhibition affects the parasympathetic and sympathetic baroreflex gain to a greater extent in SH rats than in WKY rats. This hypothesis is supported by our previous study that investigated the cardiopulmonary reflex responses to catalase inhibitor administration into the 4 th V in SH and WKY rats (37). …”
Section: Discussionsupporting
confidence: 72%
“…We therefore consider that central catalase inhibition affects the parasympathetic and sympathetic baroreflex gain to a greater extent in SH rats than in WKY rats. This hypothesis is supported by our previous study that investigated the cardiopulmonary reflex responses to catalase inhibitor administration into the 4 th V in SH and WKY rats (37). …”
Section: Discussionsupporting
confidence: 72%
“…Considering that the brain is an important regulator of the cardiovascular system,[ 28 29 ] neurophysiological hypotheses concerning the effects of music on cardiac autonomic control based on previous studies may help to explain our findings. HRV was analyzed in students listening to a story.…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, we found no acute effects of relaxant classical baroque musical auditory stimulation on the geometric indices of HRV. It was previously indicated that the intensity of the auditory brainstem responses to rising chirp stimulation is affected by the amplitude-frequency response of the earphone [ 24 ]. Considering that the brainstem regulates the cardiovascular system [ 2 , 25 , 26 ], it could be hypothesized that the use of earphones influences cardiovascular reaction during auditory stimulation.…”
Section: Discussionmentioning
confidence: 99%